Advancement of bioreactor landfill for municipal solid waste disposal - HE Ruo; SHEN Dong-sheng; ZHU Yin-mei (浙江大学学报. 农业与生命科学版)
Characteristics of bioreactor landfill and its effects on leachate and microbial communities are discussed in this paper. The main types of research on bioreactor landfill for municipal solid waste disposal are summarized and the development trend of bioreactor landfill is predicted.